Adsorption/Oxidation of Arsenic in Groundwater by Nanoscale Fe‐Mn Binary Oxides Loaded on Zeolite. (1st February 2014) - Kong, Shuqiong; Wang, Yanxin; Zhan, Hongbin; Yuan, Songhu; Yu, Mei; Liu, Mingliang
ABSTRACT: : Nanoscale Fe‐Mn binary oxides loaded on zeolite (NIMZ) is synthesized and characterized. The as‐synthesized adsorbent is amorphous with 126 m 2 /g surface area; it is effective for the adsorption of both As(III) and As(V) in synthetic groundwater. It has high adsorption capacities of 296.23 and 201.10 mg/g for As(III) and As(V), respectively. For the adsorption of 2 mg/L arsenic, the aqueous concentration quickly decreases to less than 10 μg/L within 30 min. During the adsorption of As(III), the in‐aqueous measurement of As(V) shows a low concentration in the initial stage and disappears afterward. The fraction of As(V) on NIMZ gradually increases with time, proving the oxidation of As(III). The adsorption of As(III) and As(V) decreases with increasing pH. The anions of, , and significantly compete with arsenic for the adsorption sites. The inner‐sphere surface complexes are formed by As(III) or As(V) with the hydroxyl groups on the surface of NIMZ.